(untitled) (REMUNOM, 2024)
The impacts of a sedentary lifestyle in the workplace is an extremely relevant topic in the Brazilian scenario, and it is necessary to discuss the issue, since a sedentary lifestyle causes losses for both the company and employees. Considered the disease of the millennium, a sedentary lifestyle is defined as a daily behavior of habits resulting from the comforts of modern life, as well as the lack or reduction of physical activities. The objective of this work is to discuss the impacts of sedentary behavior on workers’ lives, presenting possible solutions to reduce the problem. The work will be carried out based on analysis of bibliographical research, as well as data contained in articles. The expected results indicate that a sedentary lifestyle and work are interconnected, since the lack of exercise (one of the causes of a sedentary lifestyle) can be directly associated with the work that the person does. This is because, when employees put excessive stress on their body and mind during the workday, their willingness to exercise only tends to decrease. As a result, a sedentary lifestyle can cause a large volume of absences and sick leave among the team and to cover employee absences, the company ends up having to hire temporary workers, generating expenses on the payroll. It was concluded that the corporation has a fundamental role in the health of employees, requiring its intervention in order to reduce the sedentary lifestyle of workers, thus increasing their productivity and, therefore, improving the results they present.